2011
DOI: 10.1111/j.1651-2227.2011.02414.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain in infancy and post‐bronchiolitis wheezing

Abstract: High birth weight and the development of overweight may be associated with post-bronchiolitis wheezing in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
4
2
Order By: Relevance
“…We were not able to confirm the earlier observations that a rapid or excess weight gain in infancy increases the risk of later asthma . In this same cohort, the birth weight over 4,000 g and an excess weight gain in that subgroup before 6 months of age were associated with more post‐bronchiolitis wheezing until 1.5 years of age, but this was not anymore to be seen at the median age of 6.5 years. In a study of 197 American children at high risk for asthma, the early‐life weight gain pattern was not associated with daily asthma symptoms or lung function at 5‐ to 6‐years of age, but decelerated weight gain was associated with fewer emergency doctoral visits and less rescue treatments with corticosteroids .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We were not able to confirm the earlier observations that a rapid or excess weight gain in infancy increases the risk of later asthma . In this same cohort, the birth weight over 4,000 g and an excess weight gain in that subgroup before 6 months of age were associated with more post‐bronchiolitis wheezing until 1.5 years of age, but this was not anymore to be seen at the median age of 6.5 years. In a study of 197 American children at high risk for asthma, the early‐life weight gain pattern was not associated with daily asthma symptoms or lung function at 5‐ to 6‐years of age, but decelerated weight gain was associated with fewer emergency doctoral visits and less rescue treatments with corticosteroids .…”
Section: Discussioncontrasting
confidence: 99%
“…The cut‐off value of the z BMI for overweight was 1.16 for girls and 0.78 for boys (corresponding BMI of >25 kg/m 2 in young adults) and for obesity 2.11 for girls and 1.70 for boys (corresponding BMI of >30 kg/m 2 in young adults), respectively. Since national sex‐ and age‐specific height‐related BMI charts are available only from the age of 24 months onwards, overweight was defined as weight‐for‐length (WFL) >110% and obesity as WFL >120% at the 18‐month follow‐up visit, as published recently …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that higher birth weight was positively associated with respiratory infections in the first 2 years of life. While most studies have focused on low birth weight and respiratory morbidity in infancy, others have found the opposite, specifically that high birth weight was associated with post-bronchiolitis wheezing in infancy ( 61 ) and RSV LRTI ( 62 ). Although the mechanism remains to be elucidated, it has been suggested that macrosomia may be associated with an altered immunologic phenotype ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, being overweight (weight-for-length >110%) at 1.5 years of age was associated with recurrent post-bronchiolitis wheezing. 18 In contrast, being overweight or obese according to weight-for-length z-scores, was not significantly associated with clinical characteristics of viral acute bronchiolitis. 13 These results may differ because of the varying parameters used to define obesity in young children under 2 years of age.…”
Section: Discussionmentioning
confidence: 82%